Pengaruh Perlakuan Konsentrasi Kalsium Klorida (CaCl2) dan Lama Penyimpanan terhadap Kadar Asam Askorbat Buah Tomat (Lycopersicum esculentum Mill.) - Rahmawati, Ita Setiani; Hastuti, Endah Dwi; Darmanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
The aims of this study to determine the effect of combined treatment CaCl 2 concentration and storage time on ascorbic acid concentrations and decrease of tomatoes fruit wight as well as knowing the CaCl2 concentration effect on the long shelf life. The research using CRD factorial pattern (4 x 3). Factor I is the concentration of CaCl2 (K0: 0 M, K1: 0.05 M, K2: 0.1 M and K3: 0.15 M), factor II is a long storage Â Â Â (L1: 4 days, L2: 8 days and L3: 12 days) . The data obtained were analyzed by ANAVA at 95% significance level, followed by Duncan's test at the 95% test level. The parameter is observed levels of ascorbic acid (milligram/100gram) with iodine titration method, decrease of tomatoes fruit weight and long shelf life. The results showed the interaction between the concentration of CaCl 2 and storage time treatment on levels of ascorbic acid. CaCl2 0,1 M with 4-day old store treatment shows the amount of ascorbic acid is highest. CaCl2 treatment also affects to minimize decrease of the weight tomatoes fruit and prolong shelf life of tomatoes 5 to 8 days compared to controls.